Answer:
- the first number is 60
- the second number is 42
Explanation:
If we let x and y represent the first and second numbers, respectively, then the first sentence of the problem statement tells us ...
(1/2)x - (2/3)y = 2
The second sentence of the problem statement tells us ...
(1 -5/6)x +(1 +1/6)y = 59
Solution
Multiplying the first equation by 6 gives ...
3x -4y = 12
Multiplying the second equation by 6 gives ...
x + 7y = 354
Solving the second equation for x gives ...
x = 354 -7y
Substituting that into the first equation gives ...
3(354 -7y) -4y = 12
1050 = 25y . . . . . . . . subtract 12-25y
42 = y . . . . . . . . . . . . divide by 25
Then we can find x using its equation ...
x = 354 -7·42 = 60
The first number is 60; the second number is 42.